Communityserviceforinfantswithcleftlipand palate at Mitra Sejati andGrandmed Hospital North Sumatera - Syafrinani, Syafrinani; Chairunnisa, Ricca; Rusdy, Hendry (Indonesia Prosthodontic Association, 2021)
Cases of cleft lip and palate (CLP) in infants were many in Medan and surrounding areas.There were about 150 cases of infants with CLP in a year handled by Mitra Sejati Medan Hospital andGrandmed HospitalLubuk Pakan,butthetreatmentgiven was only surgical treatment,while the follow-up care,which isthefabricationofartificialpa-late or feeding plate before or after surgery,cannot be facilitated.Until now CLP further treatment cannot be done becausetheparentsdonotknowthetreatmentand most of them came from groups with low socio-economic level andthefabricationof feedingplaterequiredhigh costs.To overcome this problem,we held communityserviceby fabricating feeding plates as feeding aids for babies with CLP.The method used to achieve this goalofserviceis collectingdatafrompatientswithCLPinthetwohospitals,generalexaminationbypediatrician,makingtheimpression of the oral cavity to create the working cast,making outline design,doing thewaxpatternandfeeding plate fabrica-tioninthe laboratory using hard and soft acrylic materials combination.The insertion of feedingplatesisperformed at the hospital and evaluated whether the baby can drink milk normally using a bottle. Body weight changes are evaluated every month until the baby is declared ready for surgery.